Effects of different rearing systems on meat production traits and meat fiber microstructure of Beijing‐you chicken. (11th December 2014) - Fu, Dezhi; Zhang, Daixi; Xu, Guiyun; Li, Kaiyang; Wang, Qiong; Zhang, Zebin; Li, Junying; Chen, Yu; Jia, Yaxiong; Qu, LuJiang
Abstract Beijing‐you is a Chinese local chicken which is raised for both meat and eggs. In the present study, we detected the effects of different rearing systems on growth, slaughtering performances and meat quality of Beijing‐you chickens at 26–40 weeks of age. Six hundred Beijing‐you hens were randomly allocated into two groups at 16 weeks of age and raised in free range or battery cage systems. The body weight, slaughtering performance and meat quality were measured for each group at the ages of 26, 30, 35 and 40 weeks. Some of the traits were dramatically influenced by the two systems, although most of them did not show significant changes. For the meat fiber microstructure, we found that the diameter of thigh and breast muscle fiber in the free range group were significantly increased than in the cage group (P < 0.05) at 26 weeks of age. The ratio of fast muscle fiber in thigh muscle samples of the free range group was significantly reduced compared to that of cage group at both 35 (P < 0.01) and 40 (P < 0.01) weeks of age, indicating that the free range system could promote the transforming of fast muscle fiber to slow muscle fiber.